Visual acuity in controls and patients measured with Maxwellian view and a 3 mm pupil: Examining potential effects of inherent and induced aberrations - Vamsi Parimi; Ann E. Elsner; Christopher A. Clark; Brett J. King (PLoS ONE, 2026)
We sought to improve the measurement of visual acuity (VA) by reducing the effect of unwanted optical artifacts in patients with retinal disease. We evaluated the effects of age and of inherent and induced aberrations on VA for controls and patients with changes to the posterior segment, anterior segment, or both. We tested VA in 30 controls and 17 patients, using Maxwellian view and a 3 mm pupil. This method reduces wavefront aberrations and allows high spatial frequency information to be transmitted at a constant retinal illuminance. We reduced glare, crowding, and fixation errors by projecting a single letter E in a small field size. We corrected only defocus, then determined the extent to which VA and standard deviation (SD) were influenced by age and inherent wavefront aberrations (astigmatism, spherical aberration, and root mean square error higher order aberrations (RMSHO)), as well as by induced aberrations (spherical aberrations and coma). Optical coherence tomography (OCT) provided central macular thickness (CMT), which was compared to wavefront and VA results to determine the effect of retinal status. The use of Maxwellian view and a 3 mm pupil reduced aberrations, but the association between VA and inherent astigmatism ( p = 0.011) was significant for controls, although not for patients. For controls, RMSHO significantly increased with age ( p = 0.014), despite no impact on VA. Induced aberrations, which were as large as with 5 mm pupils, significantly worsened mean VA in controls ( p < 0.001) and patients ( p < 0.001), more for positive spherical aberrations than negative. Using Maxwellian view and a 3 mm pupil reduced optical aberrations and their effects on VA, important in managing patients with retinal disease. Only residual astigmatism was related to poorer VA.